PERSEPSI EMOSI KARYAWAN PASCA AKUISISI INDUSTRI PERHOTELAN DI BRUNEI - Kurnia Fadila (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2020)
The main purpose of this paper is to examine the emotional response of the employee after an acquisition; the goal is to provide useful information for Parkview Hotel’s management team on how they could evaluate change processes in the future. This study included research design as a field study using survey methodology. The study conducted at a Parkview Hotel in Brunei Darussalam, particularly in the Room Division and Food and Beverage Division. In this study, research design includes a causal relationship between two or more variables. The feeling of meaningfulness and safety has a positive impact on employee perspective as categorized as high by the average score, respectively (4.08) for meaningfulness and (4.03) for safety. The limitations of this research are mainly linked to the use of the list of eight factors that was made on the basis of the existing emotion literature to attempt to include factors, especially important for service employees in the hospitality industry. The list appears to cover the most important antecedents of emotion. However, as the knowledge regarding the specific drivers of emotion for this group of employees is limited, there is a risk that some important drivers were not included in the list. Based on the reported results, management can deliver specific recommendations regarding which areas of the employee need to pay more attention to in order to improve performance of the employee, and in order to be a better work place. This paper brings to light original and valuable findings related to the perception of the employee after showing expected results in terms of emotion after acquisition.Keyword - Employee Emotion; Acquisition; Psychological Meaningfulness; Psychological Safety.